PENGUJIAN GARCH OPTION MODEL UNTUK BARRIER OPTION DI BURSA EFEK INDONESIA - Tendi Haruman; Riko Hendrawan (Jurnal Keuangan dan Perbankan, 2009)
The purpose of this research was to test the accuracy of GARCH Option Model forpricing stock option contracted on Astra International, BCA, Indofood and Telkom when barrierexisted at The Indonesia Stock Exchange. Utilizing intraday stock movement and stock optioncontract data, simulation was conducted using actual data. To test the accuracy of GARCH OptionModel, average percentage mean squared error was used to compare simulated premiumwith its payoff at its maturity date. The findings from this research were one month optionaverage percentage mean squared error of GARCH Option Model was three point fifty onepercent (3.51%), two month option was six point sixty one (6.61%) and three month optionwas seven point seventy nine percent (7.79%).